Phaethon variability during December 2017 closest approach to Earth. (January 2019) - Lazzarin, M.; Petropoulou, V.; Bertini, I.; La Forgia, F.; Ochner, P.; Migliorini, A.; Siviero, A.
Abstract: In the course of its last close encounter with the Earth in December 2017, the peculiar Near Earth Object (NEO) 3200 Phaethon has been the target of an international observational campaign in particular connected with the proposed mission Destiny + (Demonstration and Experiment of Space Technology for INterplanetary voYage Phaethon fLyby dUSt science) by JAXA (Japan Aerospace Exploration Agency) to be launched in 2022. The nature of 3200 Phaethon is still debated because of its asteroidal dynamical behavior as opposed to its connection with the Geminid meteor shower, typical cometary residuals. Owing to its vicinity to our planet (Minimum Orbit Intersection Distance MOID = 0.0206 AU) it has been included also in the class of Potentially Hazardous objects and it has been extensively investigated also during its previous perihelion passages. It has been classified as B-type asteroid (Binzel et al., 2001), with different spectral slopes found by several authors in the wavelength region shortward 0.55 μ m . Many issues remain to be explored regarding the nature of this object and in this context we observed 3200 Phaethon in the course of 24 h during its last closest approach to the Earth. Low-resolution spectra at very high elevation angles (airmass < 1.15 ) were acquired with the 1.22–m Asiago telescope on 2017-Dec-16 and 2017-Dec-17. The variation of the viewing geometry during these observations was also derived. We found a significant variation in Phaethon spectral slope in the wavelength range [0.33–0.64] μ m during its perigeon passage. The slope varies from − 9.1 ± 0.2 % ( / 0.1 μ m ) on 2017-Dec-16 to − 2.0 ± 0.1 % ( / 0.1 μ m ) on 2017-Dec-17. This variation seems to be related to a disappearing bluer region at high latitudes ( > 70 ∘, close to the North pole). The spectra show also a weak absorption band around 0.43 μ m and lack the reflectance downturn at least until ∼ 0.33 μ m . The comparison with meteorites suggests compositional similarities with CI/CM unusual chondrites. We propose several scenarios that could be responsible for the variability recorded, such as possible surface variations in composition, grain-size, or the level of space weathering and thermal metamorphism. A strong and sudden variation of dust production is also discussed. Highlights: Significant variation in Phaethon spectral slope. Observed variation seems related to the disappearing of the northern polar region. Lack the reflectance downturn until 0.33micron. Detection for the first time of the 0.43 μm band: Phaethon hydration? Very good match with CI/CM meteorites.